Matrix metalloproteinase-9 modulates intestinal injury in rats with transmural colitis. - RADOMSKI, MAREK; MEDINA MARTIN, CARLOS (My University, 2006)
Proteolysis and degradation of extracellular matrix by metalloproteinases (MMPs) may contribute to intestinal injury in inflammatory bowel disease. In the present study, we investigated the pathogenic role of gelatinases (MMP-9 and MMP-2) on transmural colonic injury in a rat model of chronic colitis, which was induced by intracolonic instillation of trinitrobenzene sulfonic acid (TNBS). The activity and expression of MMP-2 and MMP-9 were measured in colonic tissue and peripheral neutrophils by fluorescence, zymography, Western blot, or immunohistochemistry at different time-points. Furthermore, myeloperoxidase content in colonic homogenates was analyzed to evaluate inflammation. Finally, morphological changes were assessed following early or delayed administration of CGS-27023-A, a synthetic inhibitor of MMPs. We found that the induction of colitis led to a significant up-regulation in tissue gelatinase concentration, whereas no changes in collagenase activity were observed. In addition, up-regulation of pro-MMP-9, but not of pro-MMP-2, was found on Days 7 and 10 following the induction of colitis. Furthermore, transmural MMP-9 was detected by immunofluorescent staining in the inflamed tissue. Consistent with tissue samples, neutrophils from colitic rats showed a significantly increased activity of pro-MMP-9. Finally, early but not delayed treatment with CGS-27023-A attenuated colonic mucosal injury in rats with TNBS-induced colitis. In conclusion, up-regulation of MMP-9 in peripheral and colonic neutrophils modulates transmural colonic injury in rats with TNBS-induced colitis.
Keywords: inflammatory bowel disease